Musculoskeletal emergencies - Browner, Bruce D. ;Fuller, Robert P. (Philadelphia, Pennsylvania : Elsevier Saunders, 2013)
Equip yourself with all the guidance you need to diagnose, stabilize and provide the initial management of MSK emergencies as effectively as possible. Optimize patient's disposition ranging from emergency department discharge to the operating room. A leading orthopaedic trauma surgeon and a respected emergency physician bridge the gap between these specialties to help you give these patients the best chances of favorable outcomes. Address emergency orthopaedics - both acute trauma and urgent general orthopaedic issues - at the point of care with the multidisc
General Principles of Initial Care -- Radiographic Imaging -- Infections Involving the Musculoskeletal System -- Analgesia, Conscious Sedation, Regional Blocks, and Anesthesia -- Analgesia, Conscious Sedation, Regional Blocks, and Anesthesia -- Perioperative Assessment -- Pregnancy -- Spine -- Shoulder -- Elbow and Distal Humerus -- Wrist and Forearm -- Hand and Digits -- Hip and Thigh -- Distal Femur, Knee, and Patella -- Ankle -- Foot -- Pelvis -- Introduction to Pediatric Trauma -- Pediatric Pathologic Fractures -- Pediatric Shoulder and Humeral Shaft -- Pediatric Elbow -- Pediatric Forearm and Distal Radius and Ulna Fractures -- Pediatric Hand Injuries -- Pediatric Cervical Spine Fractures -- Pediatric Thoracolumbar Spine Fractures -- Pediatric Thoracolumbar Spine Fractures -- Pediatric Fractures and Dislocations of the Hip -- Pediatric Femur -- Fractures of the Pediatric Knee -- Pediatric Tibia and Fibular Shaft and Ankle Fractures -- Pediatric Foot
Includes bibliographical references and index.
Keywords: MUSCULOSKELETAL SYSTEM -- INJURIES -- HANDBOOKS